A Trinitarian approach to spirituality: Exploring the possibilities - Venter, Rian (HTS teologiese studies, 2015)
Spirituality and ultimacy are inextricably linked. Underlying the plurality of spiritualities are myriad ways to construe the identity of the transcendent. In a Christian sense, the notion of the divine with a Trinitarian identification is central. The article examines the implications of such a naming of God for spirituality. Attention is paid to the relationship between doctrinal theology and spirituality as well as to scholarly reflection already undertaken on a so-called Trinitarian spirituality. The article suggests guidelines for future work and emphasises that an adequate account should be given of how Trinitarian theology is undertaken as symbolising and hermeneutical endeavour. Some unique features of this spirituality are profiled, and it is argued that a Trinitarian imagining of the divine may generate perspectives not possible in an unqualified monotheistic approach.